(untitled) (International Journal of Physiotherapy, 2017)
Background: The objective of this present study was to determine the Effectiveness of Floor Exercises versus Ball Exercises on spinal mobility in Spastic Diplegic. Methods: Institutional ethical committee permission was taken before starting the study. A sample of 70 Diplegic CP children was screened, and 40 meeting the inclusion criteria were selected for study were then randomly divided into two groups one control other experimental i.e. 20 in each group by chit method. Both the groups were assessed with spinal goniometry using Tape measurements for Thoracolumbar spine and Modified Schober’s Test (MMST)before and after the treatment. Control group were given Floor exercise on a mat, and Swiss ball was giving experimental group Ball exercises for ten repetitions with 10-second hold, treatment time was 40 min per session for 3days per week for six weeks. Same sustained stretching technique for both groups in bilateral lower extremities for ten repetitions with 30 sec hold was given for, TA, Iliopsoas, Hamstrings, Hip Adductor, Rectus femoris. Result: Significant improvement was noted in the Intra-group comparison of both the groups from baseline to post six weeks of intervention p-value 0.001*** in both groups, and the Intergroup analysis using with tape measurements for Thoracolumbar spine (p-value) and MMST (p-value 0.133NS). Conclusion: The present study concludes that there is a similar effect of both Floor Exercises versus Ball Exercises on spinal mobility in Spastic Diplegic.